Signals in equity-based crowdfunding and risk of failure - Felix Reichenbach; Martin Walther (Financial Innovation, 2021)
This study investigates signal validity in equity-based crowdfunding by examining whether signals that increase crowd participation are associated with higher post-offering success. Post-offering success is measured as the probability of survival. We use a hand-collected data set of 88 campaigns with over 64,000 investments and 742 updates from a well-established and leading German equity-based crowdfunding platform, Companisto. We find that indicating that the chief executive officer holds a university degree and a higher number of business-related updates are associated with a lower risk of failure, which is in line with recent research on offering success. The number of updates on external certification, promotions, and the team is associated with a higher risk of failure. In contrast to recent findings on offering success, we find that the equity share offered is positively related to post-offering success, whereas a high number of large investments or updates on campaign development are accompanied by a higher probability of failure. Our results provide guidance for entrepreneurs and investors regarding which signals are worth sending or using. Furthermore, these results suggest that investors are partly using wrong signals and challenge the rationality and wisdom of the crowd.
Keywords: D80; G33; L26; M13; 650; Equity-based crowdfunding; Post-offering success; Signaling; Startup failure; Startups; Updates